Digitalisasi dan bahasa Indonesia: Tantangan melestarikan bahasa Indonesia pada era globalisasi di sekolah dasar - Huda, Arindra Ikhwan Nur; Nisa, Ana Fitrotun; Al Masjid, Akbar (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The era globalization has an impact on culture, especially on use of the Indonesian language, particularly among students. Ease of accessing information and interacting with foreign cultures through the internet and social media often encourages use of foreign languages or mixed languages in daily communication. This phenomenon can erode the proper and correct use of Indonesian language, even potentially shifting the preference Indonesian as the primary language and identity. The purpose of this article is to preserve use of the Indonesian language among students. Eight from Kayumas 2 elementary school participated in this research. Furthermore, the data collection techniques involved interviews and active participation observations. Then, data analysis of this research includes data reduction, data presentation, and data conclusion drawing. The findings of this study indicate that parental involvement plays important role in maintaining students’ interest in using Indonesian language. Therefore, this research aims to identify specific challenges faced in preserving Indonesian language, as well as the innovative strategies implemented by teachers in facing this era globalization. The research results are expected to provide insights into efforts to preserve Indonesian language at school level and implications for character formation and national identity among students at Kayumas 2 elementary school.